যা দেখেছি যা পেয়েছি - চৌধুরী, আনোয়ারউল্লাহ (ঢাকা : অনন্যা, 2018)
Autobiographical reminiscences of Anwarullah Chowdhury, college teacher and educator from Bangladesh.
Donated By Akbar Ali Khan
In Bengali; includes passages in English.
Keywords: Chowdhury, Anwarullah; College teachers -- Bangladesh -- Biography; Educators -- Bangladesh -- Biography